2020
DOI: 10.3168/jds.2019-16398
|View full text |Cite
|
Sign up to set email alerts
|

Diet starch concentration and starch fermentability affect markers of inflammatory response and oxidant status in dairy cows during the early postpartum period

Abstract: Our objective was to evaluate the effects of diet starch concentration and starch fermentability on inflammatory response markers and oxidant status during the early postpartum (PP) period and its carryover effects. Fifty-two multiparous Holstein cows were used in a completely randomized block design experiment with a 2 × 2 factorial arrangement of treatments. Treatments were starch concentration and starch fermentability of diets; diets were formulated to 22% (low starch, LS) or 28% (high starch, HS) starch w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…Because high-concentrate feeding can result in increased plasma concentrations of lipopolysaccharide binding protein (LBP) [ 18 ], a proxy for increased LPS entry to the bloodstream (i.e., endotoxemia), we speculate that the induction of the proinflammatory state that promotes SM degradation may be the result of LPS activation of toll-like receptor-4 signaling and TNFα [ 28 ]. In line with this, ruminal acidosis induced by high-grain diets increases gut permeability, leading to endotoxemia and inflammation [ 24 , 29 , 30 ]. Similarly, we observed reduced pH in the rumen [ 18 ] and in the reticulum in cows fed the high starch diet, as well as increased levels of LBP.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Because high-concentrate feeding can result in increased plasma concentrations of lipopolysaccharide binding protein (LBP) [ 18 ], a proxy for increased LPS entry to the bloodstream (i.e., endotoxemia), we speculate that the induction of the proinflammatory state that promotes SM degradation may be the result of LPS activation of toll-like receptor-4 signaling and TNFα [ 28 ]. In line with this, ruminal acidosis induced by high-grain diets increases gut permeability, leading to endotoxemia and inflammation [ 24 , 29 , 30 ]. Similarly, we observed reduced pH in the rumen [ 18 ] and in the reticulum in cows fed the high starch diet, as well as increased levels of LBP.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, we and others have previously observed increased insulin and reduced FFA concentrations in plasma of cows fed high-starch diets [ 18 , 21 ], and a higher incidence of laminitis associated with reduced circulating sphingomyelin concentrations in fattening Holstein bulls fed a high-starch and high-protein diet [ 22 ]. In addition to limitations in substrate availability for Cer and SM synthesis, we posit that high-starch diets could potentially induce a proinflammatory status in dairy cows [ 23 , 24 ] that may in turn induce SM degradation. This mechanism appears to include the activation of acid and neutral sphingomyelinases by tumor necrosis factor α (TNFα) [ 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…High-production dairy cows typically experience high oxidative stress [ 24 ], which can be exacerbated under certain environmental, physiological, and dietary conditions [ 25 ]. Research on dairy cows has shown that the high-concentrate diets used to support the energy demands of high-production dairy cows cause remodeling of the microbial composition and function in the gastrointestinal tract of dairy cows [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the current intensive ruminant farms, increasing the proportion of rapidly fermentable carbohydrates in the diet has become a common strategy for improving the performance of ruminants. However, the rapid ruminal digestion of starch in the rumen also increases the risk of subacute rumen acidosis (SARA) [ 1 ], especially for high-yielding cows, goats and beef cattle [ 2 , 3 , 4 ]. The starch content of corn grain is 62.6% (dry matter), which is currently one main source of starch in ruminant diets.…”
Section: Introductionmentioning
confidence: 99%